2021
DOI: 10.1155/2021/1341644
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium Bromide Attenuates Mucus Hypersecretion in Patients with Stable Chronic Obstructive Pulmonary Disease

Abstract: Background. Patients with stable chronic obstructive pulmonary disease (COPD) have been observed to benefit from tiotropium bromide. However, there are few studies of tiotropium bromide on sputum and sputum viscosity. To evaluate the effect of tiotropium bromide on mucus hypersecretion, a randomized, double-blind controlled trial was performed. Methods. 120 cases of patients with pulmonary function grade II were divided into two groups, which include the treatment group given tiotropium bromide powder inhalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This study revealed that AECOPD patients with no obvious signs of infection who had thick sputum or phlegm and who are undergoing follow-up could have a poor prognosis if they did not receive early treatment with antibiotics. When the disease worsens, the volume and viscosity of mucus in the airway may further increase due to the inflammatory response secondary to infection or other stimuli (Yu et al, 2021). If there is too much mucus in the trachea or if the mucus is too thick, there can be a favorable condition for bacterial colonization in the respiratory tract, causing frequent acute exacerbation and poor prognosis in patients (Miravitlles, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that AECOPD patients with no obvious signs of infection who had thick sputum or phlegm and who are undergoing follow-up could have a poor prognosis if they did not receive early treatment with antibiotics. When the disease worsens, the volume and viscosity of mucus in the airway may further increase due to the inflammatory response secondary to infection or other stimuli (Yu et al, 2021). If there is too much mucus in the trachea or if the mucus is too thick, there can be a favorable condition for bacterial colonization in the respiratory tract, causing frequent acute exacerbation and poor prognosis in patients (Miravitlles, 2011).…”
Section: Discussionmentioning
confidence: 99%